Hecke operators on de Rham cohomology. - Lee, Min Ho (Revista Matemática Complutense, 2004)
We introduce Hecke operators on de Rham cohomology of compact oriented manifolds. When the manifold is a quotient of a Hermitian symmetric domain, we prove that certain types of such operators are compatible with the usual Hecke operators on automorphic forms.